The values and principles of justice and equity in the drafting of the judicial decision - Bermúdez Tapia, Manuel (2011)
A Court Order does not necessarily provide respect to the principles of justice and equity, mainly because it does not address the personal considerations of the litigants but only their objective elements materialized in a legal context (interests, rights, obligations). Similarly, the inflexible nature of the law, mainly due to its general quality, prevents the judge from observing a number of circumstances surrounding the conflict of interests, which may result in a valid ruling but illegitimate insofar that it fails to meet the principles of justice and fairness.